Exalting Jesus in Matthew - Platt, David, 1979- (Nashville, Tennessee : B & H Academic, 2013)
This new commentary series, projected to be 48 volumes, takes a Christcentered approach to expositing each book of the Bible. Rather than a verse-by-verse approach, the authors have crafted chapters that explain and apply key passages in their assigned Bible books. Readers will learn to see Christ in all aspects of Scripture, and they will be encouraged by the devotional nature of each exposition. Exalting Jesus in Matthew is the second volume in the series and is solely authored by Platt (best-selling author of Radical). Other projected contributors to the series include notable authors such as Russell D. Moore, Al Mohler, Matt Chandler, Francis Chan, Mark Dever, and others.
Includes bibliographical references (pages 381-384) and index.
Keywords: Bible. -- Commentaries